Blockchain based architecture to increase trustability and transparency in manufacturing - Farinha, Diogo Duarte de Abreu (2021)
As the fourth industrial revolution is now more of a reality than a mere futuristic vision, necessary changes need to be addressed in the manufacturing environment. The general inability of companies and customers to distinguish between truthful and untruthful information has opened a dangerous void; one that is often filled with fraud and greed. This, allied with the general population’s concerns over privacy and data mismanagement, has led to the birth of a new technology: blockchain. A universally accessible ledger that generates immutable data allows systems to be based on cryptography. Decentralized by nature, users no longer need to trust a centralized node with their data. The user becomes empowered as they are rewarded for participating, as opposed to a central entity reaping all of the wealth generated by the network. For companies in the manufacturing business, blockchain technology is also specially beneficial. Removing the trust factor among the actors in the horizontal integration of industry 4.0 translates to more transparency in the supply chain, which leads to a better overall vision and understanding of the product. The aim of this thesis is to implement an architecture connecting suppliers, retail and customers based on blockchain technology. Complete and reliable traceability of the product to the customer is the goal. By providing truthful information to all the actors involved in a product’s life cycle, value can be added, thus increasing transparency and trust in the whole network.